Estimating the Water Balance of Irrigated Rice Fields in Dry Season Makurdi, Nigeria - Ukpoju, Augustine; Oue, Hiroki (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
The water balance (WB) of three irrigated and isolated rice fields (1, 2, and 3) was examined during the dry season of rice cultivation in Makurdi from April 5 to May 6, 2023. Rice is mostly cultivated in the wet season, while dry season rice cultivation is limited by high irrigation costs, funding, and technical knowledge amidst vast water resources around the floodplains. Limited or no research estimates the water balance of a rice field in dry season Makurdi. WB took account of water inputs, outputs, and changes in soil water content (ΔW) in each water balance period. In Field 1, the WB showed a negative ΔW (–42.94 mm), which suggests that adequate water inputs are required to balance the water lost (outputs). The WB showed a positive ΔW of (89.36 mm and 464.75 mm) in Fields 2 and 3, suggesting that the water inputs be minimized to avoid wastage. The total irrigation in Fields 1, 2, and 3 was 499.28 mm, 1,186.95 mm, and 1,400.27 mm, respectively. The irrigation efficiency in Fields 1, 2, and 3 was 39.8%, 29.9%, and 20.9% respectively. The result indicates that Field 1’s rice cultivation can be improved by providing adequate irrigation and enhancing the soil water retention capacity, while proper irrigation scheduling can improve Fields 2 and 3 rice productivity.